Perlindungan Hukum Bagi Istri yang Tidak Nafkahi Menurut UU No. 16 Tahun 2019 - Kupang, Frisca Melati; Kasim, Nur Mohamad; Kamba, Sri Nanang Meiske (Legal Standing : Jurnal Ilmu Hukum, 2025)
Abstract This study aims to analyze the legal protection for a legitimate wife who does not receive maintenance within her marriage, specifically based on Law No. 16 of 2019 concerning Amendments to Law No. 1 of 1974 on Marriage. This research uses an empirical legal research method with a juridical-sociological approach. The research questions addressed in this study are: first, how is the legal protection for the legitimate wife’s right to maintenance in her marriage according to Law No. 16 of 2019, and second, what are the factors causing the failure to fulfill the wife’s maintenance rights within her marriage in Tombolango Village? Data was collected through interviews with relevant parties in the Tombolango Village community and by reviewing regulations such as the Marriage Law, the Law on the Elimination of Domestic Violence (PKDRT), and the Compilation of Islamic Law (KHI). The study found that although the law provides protection for the wife's right to maintenance, in practice, there are socio-economic and cultural factors that hinder the fulfillment of this right in Tombolango Village. Therefore, efforts to raise legal awareness in the community and increased oversight from authorities are necessary to protect women's rights in marriage.